IJABE is a fast-growing peer-reviewed OA journal: Updated Introduction to IJABE in 2013 - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2013)
International Journal of Agricultural and Biological Engineering (IJABE, www.ijabe.org) is a peer reviewed open access international journal. IJABE, started in 2008, is a joint publication co-sponsored by US-based Association of Agricultural, Biological and Food Engineers (AOCABFE) and China-based Chinese Society of Agricultural Engineering (CSAE). The ISSN 1934-6344 and eISSN 1934-6352 numbers for both print and online IJABE have been registered in US. Now, Int. J. Agric. & Biol. Eng (IJABE) is published in both online and print version.